Oral supplementation with fish oil reduces dryness and pruritus in the acetone-induced dry skin rat model. Issue 3 (September 2015) - Barcelos, Raquel C.S.; de Mello-Sampayo, Cristina; Antoniazzi, Caren T.D.; Segat, Hecson J.; Silva, Henrique; Veit, Juliana C.; Piccolo, Jaqueline; Emanuelli, Tatiana; Bürger, Marilise E.; Silva- Lima, Beatriz; Rodrigues, Luis M.
Highlights Fish oil supplementation improves skin n-6/n-3 ratio. Skin barrier dynamics seem to be positively influenced by skin n-6/n-3 ratio decrease. Fish oil n-3 PUFA promotes skin protection against dry skin stimulus. Fish oil n-3 PUFA accelerates skin physiology recovery from dry skin stimulus. FO n-3 PUFA has suppressive effects on the scratching behaviour induced by dry skin.